Husbandry, general care, and transportation of Xenopus laevis and Xenopus tropicalis - McNamara, Sean (Methods Mol Biol, 2018)
Maintenance of optimal conditions such as water parameters, diet, and feeding is essential to a healthy Xenopus laevis and Xenopus tropicalis colony and thus to the productivity of the lab. Our prior husbandry experience as well as the rapid growth of the National Xenopus Resource has given us a unique insight into identifying and implementing these optimal parameters into our husbandry operations. Here, we discuss our standard operating procedures which will be of use to both new and established Xenopus facilities.